Efforts to Erode Dichotomies Using Integrative Learning Models in Islamic Religious Education - Azizul Muchtar; Sunhaji Sunhaji (FONDATIA, 2022)
Science and religion have always been regarded as two conflicting and even conflicting regions. The post-new order situation gave birth to freedom of voice, thought and work which greatly influenced a person's morale towards views on the world of education. Public Public Primary School education seems to have failed to produce civilized human beings according to Islam. Islamic-based education, which was originally not in great demand, reinvented space in the eyes of the community. Both of these regions are actively involved in efforts to answer human origins and goals. Religion draws its answers from revelation and intuition, whereas science bases its beliefs on ratios and scientific reasoning. As for the efforts of science and religion to coexist, it is nothing more than an attitude of mutual respect for each region but a collaboration between the two sciences in order to erode the dichotomy in the field of education and be able to answer the times. The purpose of this writing is to attempt to erode the dichotomy of education with integrative models. The discussion shows that there are four kinds of conflicts between religion and science, namely conflict, independence, dialogue, and integration.